Corrosion survey of steel H-piles supporting a small craft harbours wharf in Trepassey, Newfoundland - Robert M. Hopkins; Craig C. Monahan (Canadian Institute of Mining, Metallurgy and Petroleum, 1990)
A corrosion survey was performed on ten selected H-piles which support a reinforced concrete wharf located at Trepassey, Newfoundland. Approximately 900 thickness measurements were taken at twelve different locations in each off our zones on the steel piles: the splash (atmospheric) zone, the intertidal zone, the low tide zone and the submerged zone. Results show that over the 2o-year life of the wharf, corrosion has been most severe in the splash, low tide and submerged zones with average corrosion rates for the flanges of 6.95, 9.45 and 6.86 mils per year (mpy}, respectively, and average corrosion rates for the webs of 5.13, 4.12 and 3.45 mpy, respectively. Minimal attack was found in the intertidal zone where the average corrosion rate was only 1.66 mpy on the flanges and 1.37 mpy on the webs. Such a pattern of attack is frequently observed f or steel piles partly submerged in seawater. The abnormally low corrosion rate associated with the intertidal zone is generally explained as being due to cathodic protection induced by the high corrosion rate in the adjacent low tide zone. Analysis of the corrosion data obtained for the Trepassey wharf would suggest that this explanation might be incorrect. An alternate hypothesis has been brought forward which better accounts for the extremely low corrosion rate observed in the intertidal zones of these piles.